The Right to Communicate as a Fundamental Principle: Internet and Participation in the Context of the Network Society, and the Public Policies for Internet Access in Brazil - Felizola, Pedro Augusto Maia (Law, State and Telecommunications Review, 2011)
This article addresses the relationship between the right to communicate and Internet access. The latter is portrayed as a technological tool for the effectiveness of the right to communicate, making it possible for individuals to participate in the network society. Therefore, it intends to answer the following questions: is it correct to state that Internet access is an indispensable way to guarantee the right to communicate? If so, what is the Brazilian situation concerning to the establishment of public policies to expand Internet access? The steps taken in order to clarify those questions start with a few notes regarding the relevance of the right to communicate in the context of the network society, in accordance with the criteria used to define a fundamental right. After brief comments on the constitutional provisions concerning the right to communicate, the network society is discussed amidst the recognition of the essential role played today by the Internet. Finally, the study analyzes some of the Brazilian public policies for expanding broadband access countrywide, in order to demonstrate, in view of the entire article, that: Internet access should be recognized as fundamental, and Brazil should enhance capacity building and empowerment of people, allowing them full and effective use of communication resources, as a consequence of the enforcement of the right to communicate.